An update on periodontic-orthodontic interrelationships - Dannan Aous (Wolters Kluwer Medknow Publications, 2010)
Talking about periodontic-orthodontic interrelationships is related primarily to the 1960s, where a generalized increase in salivary bacterial counts, especially Lactobacillus, had been shown after orthodontic band placement. The purpose of this article is to provide the dental practitioner with basic understanding of the interrelationship between periodontics and orthodontics by means of representing classical studies, and, to give an update on this topic by demonstrating the most recent opinions concerning periodontic-orthodontic interrelationships. Specific areas reviewed are the ability of orthodontic treatment to afford some degree of protection against periodontal breakdown, short-term and long-term effects of orthodontic treatment on the periodontium, and some mucogingival considerations. Topics considering orthodontic treatment in periodontally compromised patients were not included in this review. While past studies have shown that orthodontic treatment can positively affect the periodontal health, recent reviews indicate an absence of reliable evidence for the positive effects of orthodontic therapy on patients′ periodontal status. Periodontic-orthodontic interrelationships are still controversial issues. However, a standard language between the periodontist and the orthodontist must always be established to eliminate the existing communications barrier, and to improve the outcomes of the whole treatment.